Formulation, characterisation and In Vitro Simulation of gastrointestinal analysis of chewable yoghurt tablet incorporated with corncob fibre - Chan, Yong Lin (2023)
Yoghurt is a highly nutritious protein source fermented by lactic acid bacteria i.e. Lactobacillus delbrueckii subsp. bulgaricus BSL1 (ATCC® 11842™) and Streptococcus salivarius subsp. thermophilus (ATCC® 19258™). However, the drawback of yoghurt is lacks of fibre and is easily damaged by the contamination of other spoilage microorganisms if improperly handled or stored. Besides, the recent increase in illnesses associated with low fibre intake diets could be mitigated via the development of new functional foods containing both lactic acid bacteria (as probiotics) and corncobs, a high-fibre ingredient derived from the corn processing industrial waste. The main objective of this project is to develop chewable yoghurt tablet which are stable, wholesome and high in dietary fibre by imparting the low-value food waste, corncob powder. In this study, the yoghurt formulation and processing parameters from fermentation, spray drying to tablet making were studied. The effects of matrix-forming thickening agents, i.e. starch, fish gelatine and hypromellose (HPMC) on physicochemical properties (colour profile, pH, titratable acidity, initial viscosity, moisture, hardness, tensile strength, disintegration, friability, compressibility, hygroscopicity and flow properties), shelf life and the viable lactic acid bacterial count of yoghurt, yoghurt powder and chewable yoghurt tablet were studied. Furthermore, the influences of different additives on the viability of lactic acid bacteria along the processes (fermentation, spray drying and tableting) and its resistance against simulated gastrointestinal conditions were also investigated. The yoghurt was prepared with 12.5% (w/w) skim milk powder, 2.5% (w/w) additives (fish gelatine, starch, HPMC) and fermented with 4ml/L initial starter culture (L. bulgaricus and S. thermophilus) anaerobically at 38±2°C for 18 hours. The yoghurts had a high viable bacterial count (7.5-9.3 log no. CFU/ml), as well as desirable physicochemical properties including viscosity (10.33-87.33 mPa.s), pH (3.96-5.67), lactic acid content (0.23-1.13%), brightness (L*: 85.85-107.70), greenness (-a*: 2.45-5.82), and yellowness (b*: 11.96-21.44). Among the twelve yoghurt samples, the LB/ST(G) (mixed strain with 2.5% gelatine), LB/ST(H) (mixed strain with 2.5% HPMC), and LB(G) (single strain, L. bulgaricus with 2.5% gelatine) showed strong resistance to gastric acid and bile (<1 log no. CFU/ml). Furthermore, a significantly (p<0.05) high yield (91.36%) of yoghurt powder was produced via the SDB method (drying via Buchi Mini Spray Dryer B-290, inlet temperature, 110±5°C; outlet temperature, 60±5°C; feed rate, 20ml/ min) compared to SDN and freeze drying (55.30% and 88.01%, respectively). The mixed strain yoghurt powder with 2.5% fish gelatine, YP LB/ST(G) was chosen to be developed into chewable yoghurt tablet because it possessed significantly (p<0.05) high viability of lactic acid bacteria (8.9 log no. CFU/g), decent physicochemical properties such as moisture content (7.13%), pH (4.07), lactic acid content (9.05%), colour profile (L*, 99.65; a*, -0.97; b*, 8.16), great shelf life (91.5% survival rate after three months storage at 4°C) and exhibited very sturdy resistance against the simulated gastrointestinal fluids with the highest survival rate of 91.2% (p<0.05). Chewable yoghurt tablet fortified with corncob fibre, a new functional food product with high resistance to simulated gastrointestinal fluids (up to 90% survival rate) and better storage stability (up to 85% after three-months storage) than liquid yoghurt was developed via direct compression with 1MT force for 0.5 minutes. Lastly, this study showed that the dehydrated yoghurt products (yoghurt powder and chewable yoghurt tablet) were successfully produced. Yoghurt powder can be imparted into food products to increase their nutritional value and at the same time, problem of waste from the corn industry can be reduced via the development of new functional foods. Whereas, chewable yoghurt tablet could be introduced as an alternative treatment for patients who are deficient in fibre, probiotics, and protein.